An investigation on gasoline compression ignition (GCI) combustion in a heavy-duty diesel engine using gasoline/hydrogenated catalytic biodiesel blends. (September 2019) - Zhang, Yanzhi; Zhan, Liangliang; He, Zhixia; Jia, Ming; Leng, Xianyin; Zhong, Wenjun; Qian, Yong; Lu, Xingcai
Highlights: A comprehensive study on a GCI engine fueled by gasoline/HCB blends was performed. HCB with high reactivity initiates the combustion of the gasoline with lower reactivity. Suitable TIVC coupled with relatively low HCB blended ratio achieve high fuel economy. As an increase in HCB, the engine noise, CO and HC emissions can be effectively suppressed. Compared to RCCI, the GCI is less sensitive to the initial temperature with higher fuel economy. Abstract: A numerical and experimental investigation on gasoline compression ignition (GCI) combustion was performed in a heavy-duty diesel engine using gasoline/hydrogenated catalytic biodiesel (HCB) blends. The effects of HCB blended ratio, initial temperature at intake valve closing ( T IVC ) and start of injection (SOI) on performance of the GCI engine were studied in details. Additionally, the differences between GCI and reactivity controlled compression ignition (RCCI) were also explored. The results show that HCB with high reactivity initiates the combustion of gasoline with lower reactivity, and HCB blended ratio, T IVC and SOI have remarkable impacts on thermodynamic state of the fuel/air mixing and then engine performance. As HCB blended ratio increases, the engine noise, carbon monoxide (CO) and unburned hydrocarbon (HC) emissions can be effectively suppressed with the penalties of the increased nitrogen oxides (NOx ) and soot emissions. Retarded SOI results in a stable combustion, lower CO emissions while higher NOx emissions. Overall, the optimized operation range of GCI combustion is mainly limited by the engine noise, which can be relieved by multiple injection. In addition, the RCCI produces much lower engine noise compared to the GCI. However, the RCCI is more sensitive to T IVC with worse fuel economy.